The Student Experience in Winning English Competition : A Case Study at LIPS of Nurul Jadid - Anas, Wildani Nuril; Pranata, Mohammad Sofyan Adi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the success of students in English competitions at LIPS Nurul Jadid by identifying the institutional support and learning strategies involved. A qualitative case study approach was employed to explore the lived experiences of winning students within the Language and Islamic Public Speaking (LIPS) program at Nurul Jadid Islamic Boarding School. The researcher acted as the primary instrument, supported by observation, interviews, and documentation as data collection techniques. Prolonged engagement enhanced the credibility of the findings. Data were collected through two main methods: observation and interviews, which provided in-depth insight into students’ achievements and institutional contributions. Thematic analysis revealed that the extracurricular English program contributed significantly to the improvement of students’ speaking, listening, reading, and writing skills. Key enabling factors included mentoring, peer tutoring, structured coaching, and emotional encouragement. Key challenges identified were time constraints, pronunciation difficulties, and performance anxiety, which were addressed through disciplined practices, self-motivation, and collaborative support. The study concluded that the English language competition experience fostered not only linguistic competence but also students’ self-confidence, motivation, and enthusiasm for learning. These findings underscore the transformative role of performance-based extracurricular activities in shaping learners’ academic engagement and identity in a multilingual educational environment.